The understanding of the immunopathology in COVID-19 infection. (1st July 2021) - Tascioglu, Didem; Akkaya, Emre; Genc, Sema
Abstract: Coronaviruses belonging to the Coronaviridae family are single-stranded RNA viruses. The entry of SARS-CoV-2 is accomplished via ACE-2 receptors. SARS-CoV-2 infection coactivates both innate and adaptive immune responses. Although SARS-CoV-2 stimulates antibody production with a typical pattern of IgM/IgG, cellular immunity is also impaired. In severe cases, low CD4 + and CD8 + T cell counts are associated with impaired immune functions, and high neutrophil/lymphocyte ratios accompanying low lymphocyte subsets have been demonstrated. Recently, high IFN -α/γ ratios with impaired T cell responses, and increased IL-1, IL-6, TNF-α, MCP-1, IP-10, IL-4, IL-10 have been reported in COVID-19 infection. Increased proinflammatory cytokines and chemokines in patients with severe COVID-19 may cause the suppression of CD4 + and CD8 + T cells and regulatory T cells, causing excessive inflammatory responses and fatal cytokine storm with tissue and organ damage. Consequently, novel therapeutics to be developed against host immune system, including blockade of cytokines (IL-6, IL-1, IFN) themselves, their receptors or signaling pathways- JAK inhibitors- could be effective as potential therapeutics.